Project administration: methodological proposal for managing the needs of educational centers (Revista Electrónica Calidad en la Educación Superior, 2025)
This proposal aims to respond methodologically to the management of educational projects. The problem is contextualized in the evolution of education in Latin America, within a globalized world that requires project-based management strategies that specify the priorities and needs that must be addressed to achieve quality, inclusive and equitable education for all people. The type of research is descriptive, non-reactive, supported by documentary review of three educational project planning models. This constitutes a challenge that motivates the generation of initiatives by the education administration in the planning and execution of projects. In conclusion, the people involved must reflect and analyze the state of education, to implement strategic and innovative projects that empower them to be competent in the face of the challenges originated in a context of globalization.
Keywords: administration; management; educational projects; methodology; education; Latin America; competencies